ChemInform Abstract: Continuous‐Flow Hydroxylation of Aryl Iodides Promoted by Copper Tubing. Issue 49 (9th December 2014) - Cyr, Patrick; Charette, Andre B.
Abstract The rapid syntheses are performed on a gram scale in a flow system.